SOBRE OS ESPAÇOS ABERTOS DE ENTIDADE ESPECIALIZADA NA REABILITAÇÃO DE TOXICODEPENDENTES: UMA INVESTIGAÇÃO PELA QUALIFICAÇÃO DO AMBIENTE E DO PROCESSO TERAPÊUTICO - Bagnati, Mariana; Fedrizzi, Beatriz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article is part of a thesis in development, titled "Healing Garden: a Resource for Open Spaces of Specialized Institutions in Rehabilitation of Chemical dependents." It's an important part of the research that investigates, through interviews made by the researcher with patients and staff, their perception about the entity open spaces. Athwart the survey method, it will be possible to know the potentials and fragilities of this environment that, in the evolution of the thesis, will offer the project guidelines for open spaces of the genre.